2019
DOI: 10.1186/s13071-018-3223-8
|View full text |Cite
|
Sign up to set email alerts
|

NLRP3 inflammasome activation from Kupffer cells is involved in liver fibrosis of Schistosoma japonicum-infected mice via NF-κB

Abstract: BackgroundNOD-like receptor protein 3 (NLRP3) inflammasome was reported as expressed in schistosomiasis-induced liver fibrosis (SSLF). We used an NLRP3 inflammasome inhibitor, MCC950, to investigate whether it inhibited liver fibrosis, and explored the preliminary molecular mechanism.MethodsBALB/c mice were infected with 15 cercariae through the abdominal skin. They received intraperitoneal injections of MCC950 on the day of infection and at day 22 post-infection. We examined their SSLF phenotype and the effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
49
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(51 citation statements)
references
References 69 publications
(112 reference statements)
1
49
0
Order By: Relevance
“…Previous studies demonstrated that NF-κB/NLRP3 signaling pathway promoted liver fibrosis in mice 29 . Thus, we wanted to explore if the activation of NF-κB/NLRP3 signaling was involved in pulmonary fibrosis and if scutellarin regulated this pathway.…”
Section: Resultsmentioning
confidence: 94%
“…Previous studies demonstrated that NF-κB/NLRP3 signaling pathway promoted liver fibrosis in mice 29 . Thus, we wanted to explore if the activation of NF-κB/NLRP3 signaling was involved in pulmonary fibrosis and if scutellarin regulated this pathway.…”
Section: Resultsmentioning
confidence: 94%
“…The activation of NF- κ B upregulates the expression of NLRP3 protein, which subsequently promotes more production of IL-1 β and eventually leads to pyroptosis [17]. NLRP3 inflammasome activation is correlated with liver fibrosis during BDL [18].…”
Section: Resultsmentioning
confidence: 99%
“…KCs is mainly grouped into two significantly different types: classically activated M1 KCs and alternatively activated M2 KCs. iNOS is recognized in considerable number of studies as a specific expression marker of M1 macrophages, whereas, Found in Inflammatory Zone 1 (FIZZ1), arginase-1 (Arg-1) and IL-10 are those of M2 macrophages (51,52). In both the animal trial and cell trial, TGF-β1 treatment was observed to elevate the expression of M2-specific ARG-1 and the percentages of surface antigens CD203 and CD206, but lower the expression of M1-specific iNOS and the percentages of CD40 and CD86, which indicated that TGF-β1 treatment could induce M2 transformation of macrophages in cholestatic mice.…”
Section: Discussionmentioning
confidence: 99%